New Distributional Records of Eleven Plants in India, Nepal and Burma - Naithani, H. B.; Raizada, M. B. (Indian Forester, 1976)
This paper presents new distributional records of 11 plants in India, Nepal and Burma viz., 1. Acanthospermum hispidum D.C. (Compositae) which is a native of S. America, for N.W. Himalaya; 2. Acrocephalus verbenaefolius Watt ex Mukh. (Labiateae) for Central India; 3. Ageratum houstonianum Mill. (Compositae) for Punjab, Nepal and Bengal; 4. Alternanthera ficoidea (Linn,) R. Br. ex R. and S. (Amaranthaceae) for Punjab; 5. Alternanthera philoxeroides (Mart.) Griseb. (Amaran-thaceae) which is a native of S. America and a powerful aquatic pest, which sbould be eradicate from Indian soil, for Assam and Central India. 6. Argyreia involucrata Clarke (Convolvulaceae) for Orissa; 7. Borreria eradii Ravi (Rubiaceae) for Eastern India and Burma; 8. Derris macrocarpa Thoth. (Papilionaceae) for Bihar; 9. Pilea Symmeria Wedd. (Urticaceae) for Kashmir, Himachal Pradesh and Dehra Dun at an alt. of 663 m, while the species normally occurs at 1200-3600 m; 10. Silybum marianum (Linn.) Gaertn. (Compositae) for South India. This species has both medicinal and poisonous properties; 11. Solanum elaeagnifolium Cav. (Solanaceae) for Delhi and Maharashtra. It is native of N. America which has medicinal importance for the production of steroidal hormones. Notes are supplemented by remarks on synonomy, description, distribution and distinction from the allied species. Photographs of Borreria eradii Ravi and Derris macrocarpa Thoth, are also provided. Species are arranged alphabetically and specimens -are deposited in Dehra Dun Herbarium (DD).